Pengaruh Kepemilikan Manajerial terhadap Kinerja Keuangan Perusahaan: Analisis Literatur - Chandra, Cindy (CV. Kalimasada Group, 2024)
Financial performance is the ability of the company in managing and controlling resources. Indicators of capital adequacy, liquidity and profitability are often used to measure financial performance. These requirements are often determined by indicators of capital adequacy, liquidity and profitability. Methods used Qualitative techniques, literature studies, or literature studies, and literature works based on ideas presented, especially on the subject of financial management. The purpose of this article as comparing theories and research literature of all scientific publications. Based on the analysis can be concluded the performance of a company, managerial ownership, the impact of shareholder management. The results show that the ownership structure of the company has an effect on financial success this is in accordance with the ownership of managerial shareholders. Balance in companies is very necessary for effective and efficient management and can improve finances and align managerial